Institutional governance of innovations: Novel insights of leadership in Russian public procurement - Sergey Tsygankov; Vadim Syropyatov; Vyacheslav Volchik (Economies, 2021)
In the modern conditions of the post-COVID world, the transformation of the world economy in the framework of the transition to the post-industrial paradigm, and the economy of "knowledge", the national innovation system (NIS) plays a leading role in the formation of competitive sectors of any given country. Within this setting, the performance of the Russian innovation system significantly lags behind other countries and calls for modernisation based on the modern regulatory tools, policies, and world's leading trends. The direct import of institutions of foreign innovation systems demonstrates its limited effectiveness due to the incompleteness of institutions and mechanisms for regulating the institutional environment of the Russian economy. One of the generally recognised, leading, and the most "universal" instruments for implementing innovation policy by government institutions is the public procurement of innovation. The analysis of international experience shows that the implementation of the innovation policy via innovative public procurement has a highly heterogeneous landscape even in such a "cohesive" jurisdiction as those represented by the European Union (EU) as far as different types of policy dominate in different countries of the world. There is no clear trend towards the only one mainstream regulatory approach. In this context, the Russian experience demonstrates de facto the absence of any centralised, transparent, and effective policy expressed in such pseudo-innovative procurement as refuelling cartridges or car repairs. This paper identifies the existing institutional failures of the Russian NIS on the example of the regulation of innovative domestic procurement. It proposes ways to modernise the current policy based on the institutional and narrative approaches in order to foster its leading position in the international competition. This article shows the gaps in the literature in institutional governance of innovations and innovation procurement in Russia and points at directions for future research based on narrative economics. Outlining the present knowledge as a foundation for future research in institutional governance of innovations, this article holds implications for both academics and practitioners in the field of the innovation policies and public procurement.
Keywords: B52; H57; E61; O32; 330; innovation policy; institutional economics; leadership; narrative economics; national innovation system; public procurement; regulatory failure; Russia